La integración entre la espiritualidad Nueva Era y el Nuevo Management en Argentina: afinidades y tensiones = The integration between New Era spirituality and New Management in Argentina : affinities and tensions - Funes, María Eugenia (Ciencias sociales y religión, 2016)
Despite their growing impact on the different areas of social life, spiritual disciplines and practices have, mostly, only been studied for their influence in health, therapeutics and religion, leaving apart other relevant areas of influence such as education, politics and economy. Spirituality’s influence in this last dimension counts with a number of expressions among which the inclusion of spiritual techniques and discourses to management is one of the most visible. The aim of this article is to analyze the performance and the discourses of a series of conferences that promote the idea that individuals can achieve holistic development in their work. The speeches are presented by businessmen and NGO leaders interested in spirituality, and spiritual organization's leaders The public is conformed mostly by businessmen and women, and human resources’ employees from big firms located in Argentina.